CORPUS LINGUISTICS PROJECT: SEEKING THE USE OF DEMONSTRATIVE IN SONGS WRITTEN BY EMINEM - Ussolichah, Ana Nisa; Indra, Arindi; Indriani, Lilia (Universitas Ahmad Dahlan, 2021)
The object of this study is to identify the kinds of demonstrative that are used in the songs written by Eminem. In English, there is the word this, that, these, and those. Demonstratives are used to designate the place for an object, person, or thing and to indicate pronouns that have already been mentioned. The song contains lyrics and music. Songs can be used as an easy learning medium in learning a foreign language. In improving understanding of English about demonstrative, this research belongs to qualitative research to find out the dominant types of demonstrative that used in the songs by Eminem. The observation method is a method used by researchers to collect data, while the data collection technique is listening and analyzing the songs. The data obtained came from the songs contained in the album written by Eminem from 2009 to 2014. In this study, researchers looked for the most widely used demonstrative words in Eminem's song lyrics. There were 59 songs in the analysis and consisted of 5 albums. The use of demonstratives in the song is very much, especially the demonstrative